2019
DOI: 10.1371/journal.pone.0211489
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of intraocular lens dislocation: A meta-analysis

Abstract: Purpose To compare the efficacy and safety of intraocular lens (IOL) repositioning and IOL exchange for the treatment of patients with IOL dislocation. Methods We systematically searched for relevant publications in English or Chinese in MEDLINE, Embase, the Cochrane Central Register of Controlled Trials, WHO International Clinical Trial Registration Platform, Clinical Trial.gov, China Biology Medicine Database, China National Knowledge Infrastructure Database and grey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
0
10
0
9
Order By: Relevance
“…A large sample of meta-analysis showed that neither of these methods had a significant effect on postoperative visual acuity and did not increase the risk of redislocation of IOL. After the operation of intraocular lens reposition, the incidence of anterior vitrectomy and cystoid macular edema is potentially lower than that of intraocular lens replacement, and in most cases, the incision of intraocular lens reposition is smaller than that of intraocular lens replacement; As for intraocular lens replacement ,the advantage is to provide opportunities for recorrection in patients who are not satisfied with last postoperative vision correction 3 . Therefore, in the case of complete intraocular lens, capsular bag and good function of the Zonule of Zinn, intraocular lens reposition is a suitable choice for patients with satisfactory visual acuity after intraocular lens implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large sample of meta-analysis showed that neither of these methods had a significant effect on postoperative visual acuity and did not increase the risk of redislocation of IOL. After the operation of intraocular lens reposition, the incidence of anterior vitrectomy and cystoid macular edema is potentially lower than that of intraocular lens replacement, and in most cases, the incision of intraocular lens reposition is smaller than that of intraocular lens replacement; As for intraocular lens replacement ,the advantage is to provide opportunities for recorrection in patients who are not satisfied with last postoperative vision correction 3 . Therefore, in the case of complete intraocular lens, capsular bag and good function of the Zonule of Zinn, intraocular lens reposition is a suitable choice for patients with satisfactory visual acuity after intraocular lens implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The early IOL dislocation often occurs due to improper IOL fixation and intraoperative complications and late dislocation occurs three months or later after surgery as a result of progressive zonular weakness, capsular contraction syndrome, physical labor that causes high intraocular pressure and trauma 2 . The surgical treatment of patients with IOL dislocation includes IOL reposition and IOL replacement, but the optimal management for IOL dislocation need to be considered comprehensively 3 . To the best of our knowledge, this is the first study to report late IOL dislocation caused by a deformed haptic piercing through the iris.…”
Section: Introductionmentioning
confidence: 99%
“…Наибольшее распространение получили модели ИОЛ с двумя незамкнутыми опорными элементами. В случаях замены переднекамерной или зрачковой ИОЛ вследствие позиционных осложнений (дислокация, децентрация) появилась возможность реимплантации с использованием ИОЛ из полиметилметакрилата с двумя гибкими опорными элементами, а в последующие годы эластичных ИОЛ, которые располагаются в цилиарной борозде с бесшовной или дополнительной шовной фиксацией [23][24][25][26].…”
Section: обзоры литературы Literature Reviewsunclassified
“…Исключения бывают, но они весьма редки. Реимплантация ИОЛ с фиксацией гаптики в цилиарной борозде принципиально может быть разделена на две главные методики без дополнительной шовной фиксации и с дополнительной транссклераль-ной шовной фиксацией [1,26,28]. В свою очередь все способы транссклеральной фиксации при реимплантации ИОЛ различают по способу проведения нитей ab interno [29][30][31] или ab externo [31][32][33], каждый из которых имеет свои плюсы и минусы и соответственно сторонников их использования среди хирургов.…”
Section: обзоры литературы Literature Reviewsunclassified
See 1 more Smart Citation